Utilizing the ‘Words of the Day’ Strategy to Enhance Students’ Vocabulary Skills - Godman Caupayan; Joey S. Revelo (Journal of Research in Education and Pedagogy, 2025)
Vocabulary development remains a critical concern among students in the Philippines. Despite ongoing efforts to enhance language education, many students struggle to achieve satisfactory vocabulary proficiency, which significantly impacts their overall language skills. Vocabulary acquisition is fundamental to developing reading comprehension, writing, and effective communication. This study investigates the effectiveness of the “Words-of-the-Day” strategy in enhancing students’ vocabulary, building on previous research that underscores the importance of vocabulary development in overall language proficiency. The general objective of the research was to evaluate whether this strategy could significantly improve vocabulary skills among students. Conducted during the 2023–2024 school year at Ozamiz City National High School, the study employed a quasi-experimental design involving both a control group and an experimental group. Participants were selected through purposive sampling, comprising students from two comparable classes with similar academic abilities. The primary instrument for measuring vocabulary proficiency was a standardized vocabulary test administered before and after the intervention. Data analysis involved paired t-tests to compare pre- and post-intervention scores within groups and independent t-tests to assess differences between the control and experimental groups. The findings revealed that while the control group exhibited a significant improvement in vocabulary scores post-intervention, the experimental group demonstrated a more substantial enhancement, with students achieving higher performance levels overall. This supports the conclusion that the “Words-of-the-Day” strategy effectively enhances vocabulary skills and boosts confidence in language use. Based on these findings, it is recommended that educators integrate the “Words-of-the-Day” strategy into the regular curriculum to foster better vocabulary acquisition and long-term language development among students.